Pengaruh derajat kelainan refraksi dan penggunaan kacamata koreksi terhadap ketajaman stereopsis pada anak - Dian Hidayati; Noor Syamsu; Marliyanti N Akib (Majalah Oftalmologi Indonesia, 2017)
Introduction : The stereoacuity depends on the binocular cooperation of both eyes and the good visual acuity of each eye. The relationship between stereoacuity and visual acuity is stereoacuity will decrease if the visual acuity decreases. Method : This study is a cross-sectional analytic study, conducted in elementary schools in Makassar for 3 months. There were 261 children who met the inclusion criteria consisting of 124 men (47.5%) and 137 women (52.5%). The degrees of refractive error were divided into mild, moderate, and severe degrees. Measurement of stereoacuity using Titmus Stereotest before and after the use of corrective glasses. Result : The results showed a significant correlation between the degree of refractive abnormality with stereoacuity before corrective glasses based on Kendall’s tau b = 0.313 (p <0.001), whereas the more severe of the degrees of the refractive error, the worse the stereoacuity . There is a significant correlation between the degrees of refractive error and stereoacuity after corrective glasses based on Kendall’s tau b = 0.235 (p <0.001), whereas the more severe of the degrees of the refractive error, the worse stereoacuity. There were significant differences in stereoacuity to the degrees of refractive error before and after the use of corrective glasses based on McNemar statistical test (p <0.001). Conclusion : The more severe of the degrees of the refractive error, the worse the stereoacuity. Stereoacuity after the use of corrective glasses is better than before the use of corrective glasses.